Strategi Peningkatan Kualitas Hubungan Keluarga dalam Situasi Suami Bekerja di Luar Negeri - Putri, Nyimas Lidya; Rahmaningsih, Aziza Aziz; Isanti, Hanisah Nurhalimah; Sudirman, Sudirman (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
The problem that arises is how to produce concrete sweats to produce a samawa family in a situation where the hubby works abroad. Families left at home must face colorful changes in their family dynamics, and it's important to identify strategies and sweats that can help them maintain balance and harmony in the family. The exploration system is written descriptively qualitatively, empirical normative exploration system, using field data (field exploration). The normative exploration was carried out grounded on scientific journal material related to perfecting the quality of family connections. In qualitative exploration, this study aims to explain strategies for perfecting the quality of families whose misters work abroad. The way to apply it in forming a sakinah family is by fulfilling each other's rights and scores as hubby and woman. By means of family time, and dividing each other's tasks or places in taking care of the manage. occasionally they feel lonely when they're far down from their children, still, communication between parents and children still goes well. It's carried out well and forming a sakinah, mawadah, warahmah family can also be formed on the base of strong religion, an open station towards each other, an station of honesty, and forbearance tutored to children and other family members and always be thankful for the blessings and food that Allah SWT has given us.